(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article covers the components of Uzbek sign language and serves as a guide for students of the training system of sign language interpreters. This article is intended for pedagogues of the special education system, as well as teachers of general schools where inclusive education is introduced, who deal with the problems of education of deaf and hard-of-hearing children. Sign language and the working system for teaching it are covered in detail.